The Function of Judicial Dissent in Indonesiaâs Constitutional Court - Butt, Simon (Constitutional Review, 2018)
Indonesian judges are permitted to issue dissenting opinions. Constitutional Court judges regularly hand them down. However, neither judges nor academics have outlined the purposes of dissenting opinions in Indonesia. This article aims to promote discussion about what these purposes are, or should be, in Indonesia, with a view to increasing the utility of dissents. It begins by considering the international scholarly literature details some purposes recognised in other countries, such as increased transparency and accountability, but also some disadvantages, such as the perceived weakness of a divided court. It then considers how the Constitutional employs dissents, before exploring some of the uncertainties and unanswered questions about dissents and their use in Indonesia.